Activation and selection of arithmetic facts: The role of numerical format. - Megías, Patricia; Macizo, Pedro (Memory & Cognition, 2016)
We examined the role of numerical format in the activation and selection of arithmetic facts. We also explored the inhibitory nature of this mechanism. To this end, in two experiments we manipulated the format of the operations (digit format and word format) while participants decided whether simple additions were correct or not. In Experiment 1, when an addition was incorrect but the result was that of multiplying the operands (e.g., 2 + 4 = 8), participants took more time to respond relative to a control condition where the addition's result was incorrect but unrelated. Afterward, participants took more time to respond when the result of multiplying the operands was presented again in a correct addition problem (e.g., 2 + 6 = 8), suggesting that the related multiplication result in the previous trial (e.g., 8) was inhibited to select the correct response (e.g., 6); thus, when it was presented again in the next problem, additional time was necessary to reactivate it. These effects were found in the digit format but not in the word format. In Experiment 2, we considered the degree to which participants used memory retrieval to perform the task. In participants with high retrieval usage, the interference effects in the first and second trials were larger for the digit format than for the word format. However, the participants with low retrieval usage showed interference effects only for problems with digits. These findings are discussed in terms of automaticity in retrieving arithmetic facts to perform simple arithmetic.